Raising the pH of the Pulsing Solution Improved the Acropetal Transport of NAA and 2,4-D and Their Efficacy in Reducing Floret Bud Abscission of Red Cestrum Cut Flowers - Abebie, Bekele; Philosoph-Hadas, Sonia; Riov, Joseph; Huberman, Moshe; Goren, Raphael; Meir, Shimon (Frontiers in Plant Science, 2020)
The use of auxins to improve the vase life of cut flowers is very limited. Previous studies demonstrated that a pulse treatment of Red Cestrum (Cestrum elegans Schlecht.) cut flowers with 2,4-dichlorophenoxyacetic acid (2,4-D) significantly reduced floret bud abscission, whereas 1-naphthaleneacetic acid (NAA) was ineffective. This difference resulted, at least in part, from the higher acropetal transport capability of 2,4-D compared to that of NAA. The present research focused on examining the factors affecting the acropetal transport, and hence the efficacy of the two auxins in reducing floret bud abscission of Red Cestrum cut flowers. We assumed that the differential acropetal transport capability of the two auxins results from the difference in their dissociation constants (pKa), with values of 2.75 and 4.23 for 2,4-D and NAA, respectively, which affects their pH-dependent physicochemical properties. Thus, increasing the pH of the pulsing solution above the pKa of both auxins might improve their acropetal movement. Indeed, the results of the present research show that raising the pH of the pulsing solution to pH 7.0 and above improved the efficacy of the two auxins in reducing floret bud abscission, with a higher effect on 2,4-D than that on NAA. Raising the pH of the pulsing solution decreased the adsorption and/or uptake of the two auxins by the xylem cells, leading to an increase in their acropetal transport. The high pH of the pulsing solution increased the dissociation and hence decreased the lipophilicity of the auxin molecules, leading to improved acropetal movement. This effect was corroborated by the significant reduction in their 1-octanol/water partition coefficient (KOW) values with the increase in the pH. A significant increase in the CeIAA1 transcript level was obtained in response to 2,4-D pulsing at pH 7.0 and 8.25 and to NAA pulsing at pH 8.25, indicating that the acropetally transported auxins were taken up by the cells under these conditions. Our data suggest that raising the pH of the pulsing solution would significantly contribute to the increased efficacy of auxins in improving the vase life of cut flowers.